Influence of Obesity on Clinical Manifestations and Response to Therapy in Cutaneous Leishmaniasis Caused by Leishmania braziliensis - Lago, Tainã (2021)
Brazilian Ministry of Science, Technology, and Innovation; the Brazilian Research Council (CNPq); and the Fundação de Amparo à Pesquisa do Estado da Bahia (FAPESB).